Non-parametric analysis of bank merger gains: The case of Vietnam - Phuong Anh Nguyen; Linh Dan Pham; David McMillan (Cogent Business & Management, 2020)
Over the last years, the banking sector in Vietnam has been going through the restructuring period, in order to cope with non-performing loans and build up mergers and acquisitions. This paper applies the non-parametric method proposed by Bogetoft and Wang in 2005 to evaluate the bank merger gains in Vietnam during the period 2010–2016. The potential gains from mergers are thus estimated and decomposed into technical efficiency, scale efficiency and harmony effect. The results indicate that under the production approach, all six mergers obtain potential gains with the main sources from technical efficiency and harmony effect. Under the intermediation approach, five mergers exhibit potential gains with the main source from harmony effect, while technical efficiency contributes to the potential gain of two mergers. Accordingly, banks could benefit from the new management or learn from the more efficient ones and reap benefits from harmony effect by reallocating the service portfolio of related parties in the merger to boost their activities. The post-merger efficiency scores are also calculated and are found to increase slightly compared to the efficiency scores before merger, which supports the statement that mergers help banks improve their efficiency. This paper contributes to the gap of lacking analysis on mergers and acquisitions in Vietnam banking sector.
Keywords: G21; G34; L11; L22; P41; 650; Vietnam commercial banks; mergers; potential gains; technical efficiency; scale efficiency; harmony effect